Samāja sudhāraka Īśvaracandra Vidyāsāgara - Vahorā, Rasūlabhāī Na. (Rasūlabhāī Nabījī), 1902-1958 (SAMP early 20th-century Indian books project ;, 1940)
Biography of Īśvaracandra Bidyāsāgara, 1820-1891, educationist, social reformer, and philanthropist of Bengal.